441 INTRAUTERINE GROWTH RETARDATION MODULATES SIRT1 DEACETYLASE, FOXO3 TRANSCRIPTION FACTOR, AND SUPEROXIDE DISMUTASE 2 EXPRESSION IN THE POSTNATAL CEREBRAL CORTEX. Issue 1 (1st January 2007) - Caprau, D.; O'Grady, S.; Calloway, C.; Hale, M.; Ke, X.; Yu, X.; Men, P.; McKnight, R.; Lane, R. H.
Abstract : Background: Uteroplacental insufficiency and subsequent intrauterine growth retardation (IUGR) alter cerebral postnatal gene expression and increase the risk for neurodevelopmental morbidities. IUGR causes histone hyperacetylatilation in d0 and d21 hippocampus of IUGR male rats. SIRT1, a NAD-dependent histone-deacetylase, has an important role in chromatin silencing, genome stability, neuronal protection, and longevity. SIRT1deacetylates the FOXO3 transcription factor and as a result prevents FOXO3-mediated apoptosis and stimulates FOXO3-mediated resistance to oxidative stress. Deacetylated FOXO3 up-regulates SOD2 expression. Objective: We hypothesize that IUGR decreases postnatal SIRT1 mRNA and protein levels and as a result decreases SOD2 gene expression. In this study, we analyzed SIRT1, FOXO3, and SOD2 mRNA expression and protein levels in cerebral cortex of IUGR rats. Methods: To test our hypothesis, we used term pups from an IUGR model obtained by bilateral uterine artery ligation. Pups from sham surgeries were used as controls. Protein and mRNA levels were measured on d0 and d21 by performing real-time RT-PCR and Western blot analysis, respectively. Results: SIRT1 protein levels decreased to 73.33% of controls in IUGR d0 males ( p = .023), followed by SIRT1 decreased mRNA levels (84% of controls) on d21. This is associated with a significant decrease in SOD2 mRNA levels ( p = .013, 62.66% of controls) in IUGR d21 brains with a predominant effect in males ( p = .01, 61.2% of controls). On day 21, there is also a decrease in IUGR FOXO3 mRNA levels ( p = .012, 86.8% of controls) without a significant difference between genders. Conclusion: We conclude that IUGR decreases SIRT1 gene expression in male rats, which subsequently decreases SOD2 mRNA levels. This finding may explain the neurologic morbidities and the hippocampal hyperacetylation in d0 and d21 IUGR males, which does not persist in the females. We speculate that alterations in SIRT1 gene expression early in life may contribute to changes in histone acetylation, oxidative stress resistance, and apoptosis that contribute to the long-term neurologic morbidities of the IUGR fetus.